Freedom of religion or belief an international law commentary - Bielefeldt, Heiner 1958-; Ghanea, Nazila; Wiener, Michael 1975- (Oxford Oxford University Press, 2016)
This commentary on freedom of religion or belief provides a comprehensive overview of the pressing issues of freedom of religion or belief from an international law perspective
Includes bibliographical references (pages 593-609) and index. - Description based on print version record
Keywords: Freedom of religion (International law); Human Rights; Freedom of religion (International law)